The genus Benthofascis (Gastropoda: Conoidea): A revision with descriptions of new species - Tucker, J. K.; Tenorio, M. J.; Stahlschmidt, P. (Zootaxa, 2011)
The conoidean gastropod genus Benthofascis Iredale, 1936 is examined. This genus of Conorbidae has extant species. Three previously described species from the Recent including the type species B. biconica (Hedley), B. sarcinula (Hedley), and B. lozoueti Sysoev & Bouchet are reviewed. Three new species from the Recent, B. conorbioides sp. nov., B. pseudobiconica sp. nov., and B. angularis sp. nov. are described from Australia. One of these (B. angularis) is the first Benthofascis species described from Western Australia. Two fossil species originally described as Conorbis from the Miocene and Oligocene of Australia (C. atractoides Tate and C. otwayensis Long, respectively) are for the first time assigned to Benthofascis, thus extending the geologic record of the genus to the Oligocene.